Effects of affective valence on a mixed Spatial Correspondence Task: a reply to Proctor (2013) - Erick Q. Conde (Psychology & Neuroscience, 2014)
The present study investigated the influence of emotional valence on the spatial stimulus-key location correspondence effect in three experiments using the Affective Spatial Correspondence task (AffSCt). We initially reanalyzed the results of Conde et al. (2011) according to the model proposed by Proctor (2013). In that study, compatible and incompatible responses were chosen according to the participants’ team preference. In one block, the volunteers had to press a key on the same side for the Favorite team and on the opposite side for the Rival team. In another block, a reverse code was used. We found that responses were faster for the Favorite-compatible/Rival-incompatible condition (614 ms) compared with the Favorite-incompatible/ Rival-compatible condition (691 ms). The same experimental arrangement was replicated in another Brazilian city, and similar results were found. Additionally, we employed non-affective “fake” soccer teams as a control condition, and no mapping- rule effect was observed. Finally, a final experiment that used the same design but different non-affective stimuli (yellow and blue bars) was performed to provide further evidence that the valence effect in the present experimental paradigm only occurs with affective stimuli. As expected, non-affective stimuli did not produce an overall advantage for any mapping rules, corroborating earlier findings with similar mixed designs. The results confirmed the previous findings and validity of the AffSCt as a methodology to investigate the effects of emotional valence on stimulus-response correspondence. However, we are unable to provide a conclusive explanation to support the several hypotheses proposed previously in our paper and by Proctor (2013).